2022
DOI: 10.3390/horticulturae8050435
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Pre-Harvest Supplemental Lighting with Different Light Emitting Diodes Improves Greenhouse Lettuce Quality

Abstract: Winter–spring greenhouse vegetable production is limited by low-level natural light, resulting in decreased growth and quality. To investigate whether short-term pre-harvest supplemental lighting (SL) with light emitting diodes (LEDs) can address this issue, a study was conducted in a greenhouse in Dallas, Texas. Red leaf lettuce (Lactuca sativa L. ‘Red Mist’) plants grown in a hydroponic system were treated with daytime or nighttime SL with red (R) and blue (B) LEDs (RB-LED), blue and UVA LEDs (B/UVA-LED), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Although the above-recommended UV dose is not higher than the usual outside UV intensity, care must be taken for the safety of greenhouse staff with supplemental UV lighting. Nighttime supplemental lighting in red lettuce was more effective than daytime supplemental lighting, as it resulted in better crop quality [31]. In addition, the application of shortduration supplemental blue LED light may become more effective in the pigmentation of red lettuce if applied during night breaks [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although the above-recommended UV dose is not higher than the usual outside UV intensity, care must be taken for the safety of greenhouse staff with supplemental UV lighting. Nighttime supplemental lighting in red lettuce was more effective than daytime supplemental lighting, as it resulted in better crop quality [31]. In addition, the application of shortduration supplemental blue LED light may become more effective in the pigmentation of red lettuce if applied during night breaks [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adding UVA (5-7% of photosynthetic photon flux density) to blue-LEDs reduced plant height for some microgreen species [14]. Our recent study found that short-term preharvest lighting treatment with UVA/Blue LEDs (containing both UVA and blue wavelengths) increased the antioxidant concentrations of greenhouse-grown lettuce plants without compromising plant growth and biomass [15,16]. To the best of our knowledge, the effects of adding UVA to W-LEDs on the growth and quality of indoor microgreens, for either the whole production period or at the end, remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-harvest is a practical method that can help to improve the quality and shelf-life of vegetables and reduce their risk before harvest [9][10][11]. For example, Gil [9] studied pre-harvest related to agricultural practices, including type and rate of fertilization, irrigation, and salinity, which affect fresh-cut quality, and found that pre-harvest factors increased the quality of fresh-cut lettuce and baby leaves.…”
Section: Introductionmentioning
confidence: 99%